Estudio comparativo del índice de rentabilidad en dos sistemas de cultivo de camarón blanco - García Mogrovejo, Heiner Anibal (2008)
A comparative study of the index of profitability in two systems of farming of white shrimp in function of the time of crop was carried out in a shrimp farm of the Jambelí Island of El Oro province. The objectives of this work were: 1) To determine which of two study systems [105 days (PI) and 154 days (PII)] present better capital rotation. 2) Based on the operation costs, to establish which of the two systems is more advantageous. 3). To evaluate the best produc- tion system according to the obtained profitability. For the study was analyzed the production of 4 ponds in which the handling difference was the time of farming, divided into two treat- ments with two replications. The operation capital was for the PI 28 769,61 and for the PII 32 053.91, being the difference of these costs statistically significant. The production ex- penses per pound of shrimp were respectively of 0,65 cents and 0,77 cents of dollar for PI and PII. The internal rate of return was of 64 % for PI and of 50 % for PII. It was concluded that the handling of 105 days is more advantageous for the capital rotation and the operation ex- penses, and that the best profitability is obtained with 105 days.